Marketing analysis in increasing the number of visitors at Medan Zoo tourist attractions - Yanti, Aprilda; Chairia, Chairia; Cahyati, Suci (Junal Ilmu Manajemen, 2024)
This study examines the impact of distribution channels and product quality on the This research was conducted to analyze marketing management at the Medan Zoo tourist attraction to make it more comprehensive and targeted, so that Medan Zoo can increase its attractiveness, attract more visitors, and increase its income and operational sustainability. This research uses a qualitative approach with descriptive research type. Determining informants in this research used purposive sampling. The informants who will be interviewed are the counter guards and managers, and the local community. The types and sources of data used in this research are primary data and secondary data. In this research, the data collection methods used are observation, interviews and documentation. The results obtained in this research indicate that there is a need for more interesting marketing strategies, such as actively using social media which is very influential in the business world in today's era, apart from that by providing education, entrance ticket promotions and tourism activity events at Medan Zo.